(untitled) (Research, Society and Development, 2021)
This study aims to identify in the literature the main actions developed by the nursing team at home, to offer quality of life and improve the prognosis of people with leprosy, pointing out the importance of practicing self-care. This is a descriptive review of qualitative character, data collection occurred in the following databases: LILACS; BDENF and ScieLO. The descriptors “Home Nursing Care; Leprosy; Self-care" located in the list of Health Sciences Descriptors (DECs), and took place from June to July 2021. In the first stage of the research, 107 studies were identified, which after applying the inclusion and exclusion criteria, the final sample was concluded with a quantitative of 7 studies used in the research. The main difficulty established for effective home care was the lack of preparation of the health team and lack of information on the part of the leprosy patient. In addition, the lack of adherence to the MDT system is also pointed out as one of the main risk factors triggering complications. Therefore, the need for health promotion in all axes of care was evidenced, especially practices aimed at home care, and the training of the health team to carry out activities at home effectively.